THE EFFECT OF MOTIVATION AND COMPENSATION ON JOB SATISFACTION WITH COMMITMENT AS A MODERATING VARIABLE - Hendri Khuan; Ary Subiyantoro; Muhaimin Muhaimin; Rieneke Ryke Kalalo; Matiti Kalempouw (JURNAL ILMIAH EDUNOMIKA, 2024)
Abstract There are several things that can affect employee job satisfaction in a company such as motivation given by colleagues and superiors, compensation for completing work and certain targets, and strengthened by the commitment that exists in the employees themselves. This study aims to examine the effect of motivation and compensation on job satisfaction with commitment as a moderating variable. This research is a quantitative research with an explanatory approach that uses primary data on Bank BCA employees with a minimum criteria of having worked for more than one year spread throughout the islands of Indonesia as many as 250 people. Data is distributed through questionnaires and analyzed using smart PLS 3.0. The research results show that motivation and compensation have a positive and significant effect on job satisfaction. Interestingly, after being moderated by the commitment variable, the effect of compensation and motivation on job satisfaction is increasingly significant. Keywords : Motvation, Compensation, Commitment, Satisification